Letter (translation) - Tomás, Pascual, 1893-1972
026-0127-001 TRANSLATION OF LETTER FROM PASCUAL TOMAS-TAENGUA. Comrade Walter Citrine, London. Dear Friend, After a terrible calvary I arrived at Toulouse very sick. I beg you to do something to prevent the police from molesting me and so that I can seek a little life. Nothing is known of my wife nor of my daughters who have been left abandoned in Spain. I have lost everything - house, books, clothes, records, etc. I am in misery. Write to me at the following address:- Rene Desbals, Secretary of the the Socialist Party, S.F.I.O., Rue Taur, Toulouse. Cordial greetings, (Signed) P. TOMAS. 292/946/26/127